Prevalencia de hipertensión arterial en la parroquia El Sagrario de la ciudad de Loja - Solano Paute, María Elena (2019)
High blood pressure (HBP) is considered as a public health problem associated with morbidity and mortality. The purpose of the present investigation was to identify the prevalence of hypertension according to grade, age group, gender; establish the main risk factors associated with hypertension; and compare risk factors of the global hypertensive population (constituted by diagnosed and undiagnosed hypertensive patients) with risk factors of the non-hypertensive population in El Sagrario parish. The study was a descriptive, prospective cross-sectional study, with a sample of 376 participants, who were administered a survey of 22 questions, blood pressure (BP) measurement three times separated by an interval of 1-2 minutes and getting anthropometric measurements to classify blood pressure levels, the "Clinical Practice Guideline of the European Society of Hypertension (ESH) / European Society of Cardiology (ESC) 2018 for the management of HTN" were used. As a result, the prevalence of HBP was 27.9% (n = 105), 66% (n = 69) corresponding to the female sex and 34% (n = 36) to the male. In women, the most frequent grade of BP was isolated systolic hypertension 12.4% (n = 13), while in men the normal high pressure was 5.7% (n = 6), both in those older than 66 years; Regarding risk factors, the main ones were family history, body mass index (BMI)> 25 and low physical activity. With the data obtained, the high prevalence of HBP was established, as well as the risk factors, which are mostly modifiable. Key words: blood pressure, risk factors, body mass index, physical activity.